High-resolution MR neurography follow-up of SARS-CoV-2 vaccination-associated neuralgic amyotrophy: brief communication - Mooshage, Christoph; Kele, Henrich; Bendszus, Martin; Schwarz, Daniel (Annals of Clinical and Translational Neurology, 2023)
Little is known about the value of high-resolution follow-up imaging in patients with neuralgic amyotrophy (NA) and the question of the best treatment algorithm remains unclear. Three patients (one female, two male) with the clinical presentation of SARS-CoV-2-vaccination-associated NA underwent initial magnetic resonance neurography (MRN) imaging and follow-up examinations. All patients showed a marked clinical improvement, independent of treatment, including an almost full recovery of motor function over the course of 8-12 months which was accurately mirrored by imaging findings on MRN. MRN imaging is a valuable tool for monitoring the further clinical course of patients suffering from vaccination-associated NA.